ANALYSIS OF LINK AND MATCH POLICY IMPLEMENTATION ON HUMAN RESOURCE DEVELOPMENT IN NON-FORMAL EDUCATION - Irfan Ardi; Joni Rahmat Pramudia; Viena Rusmiati Hasanah (Jurnal Scientia, 2023)
Human resource development aims to increase their abilities so that they can be used in the industrial world and help them do their jobs through the education process. Human resource development is a systematic and planned activity aimed at developing employees to improve the skills and competencies needed according to work demands, both now and in the future. The lack of human resources will result in an increase in the number of unemployed in Indonesia, because one of the factors for the increase in unemployment is caused by a decrease in the quality of human resources, making it difficult to get a job due to a lack of expertise in work needs. In facing the world of work and industry, the government provides answers related to current problems with the Link and match policy. This link and match policy creates graduates with expertise and skills in working in accordance with industry standards and the world of work and this policy can be applied to non-formal education such as courses and training institutions or other similar units.